Identification of Ectoparasites and Gastrointestinal Tract Endoparasites in Stray Cats at Traditional Market of Bojonegoro City - Karina Rachmawati; Setiawan Koesdarto; Iwan Sahrial Hamid; Dian Ayu Permatasari (Journal of Parasite Science (JoPS), 2022)
ABSTRACT This study aims to determine the ectoparasites and endoparasites on gastrointestinal tract that infest stray cats in Bojonegoro traditional market. The samples in this study were ectoparasites and feces from 40 stray cats in Bojonegoro traditional market. The ectoparasite samples were examined using the permanent attachment method without staining, while the feces samples were examined using three methods, namely native, simple sedimentation and fulleborn floatation. A positive sample is considered if a parasite is found that matches the characteristics of a parasite in cats sourced from scientific references. The results of the examination of 40 stray cats found 27 positive ectoparasites, 23 positive worms and 6 positive protozoa. The types of ectoparasites found were Ctneocephalides felis (67.5%), Otodectes cynotis (15%) where age and gender did not affect the prevalence, while the endoparasites found were Toxocara cati (42.5%), Ancylostoma sp. (22.5%) and Isospora felis (15%), age has effect on the prevalence obtained and sex has no effect . Keywords : Stray cats, Ectoparasites, Endoparasites in gastrointestinal tract